2021
DOI: 10.52547/ijimes.1.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Cell Production System Design: A Literature Review

Abstract: In a cell production system, a number of machines that differ in function are housed in the same cell. The task of these cells is to complete operations on similar parts that are in the same group. Determining the family of machine parts and cells is one of the major design problems of production cells. Cell production system design methods include clustering, graph theory, artificial intelligence, meta-heuristic, simulation, mathematical programming. This article discusses the operation of methods and researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 144 publications
0
5
0
Order By: Relevance
“…According to the obtained efficient solution, it is observed that the total cost, the amount of GHG emission, and the maximu m working hours of drivers are 45305, [20,25] ~๐‘ˆ [25,30] ~๐‘ˆ [30,35] ๐‘‡ ๐‘˜,๐‘™,๐‘ฃ , ๐‘‡ ๐‘™,c,v ~๐‘ˆ [10,15] ~๐‘ˆ [15,20] ~๐‘ˆ [20,25] ๐ถ 252, and 46, respectively. Therefore, Figure 2 shows the output variables of the problem based on the solution obtained from the neutrosophic fuzzy programmin g method.…”
Section: Solving the Small-sized Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the obtained efficient solution, it is observed that the total cost, the amount of GHG emission, and the maximu m working hours of drivers are 45305, [20,25] ~๐‘ˆ [25,30] ~๐‘ˆ [30,35] ๐‘‡ ๐‘˜,๐‘™,๐‘ฃ , ๐‘‡ ๐‘™,c,v ~๐‘ˆ [10,15] ~๐‘ˆ [15,20] ~๐‘ˆ [20,25] ๐ถ 252, and 46, respectively. Therefore, Figure 2 shows the output variables of the problem based on the solution obtained from the neutrosophic fuzzy programmin g method.…”
Section: Solving the Small-sized Problemmentioning
confidence: 99%
“…The variety of this problem is so great that it is challenging and timeconsuming to classify them and express the various states in which it occurs. Since its inception in the 1960s, many extensions have been derived based on their different applications in the real world as there are now versions, such as heterogeneous type [7], simultaneous receipt and delivery [8], open type [9], and others [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the daily increase in data production on the Internet and the advent of IoT devices worldwide, artificial intelligence is emerging to provide its countless capabilities with IoT connectivity [5]. It is important to note that IoT applications require a data-driven culture of analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The current component makers, who once entered this thriving industry as entrepreneurial organizations or small companies and have mainly expanded their activities, are influenced by environmental factors such as global recession, currency fluctuations, and methods of sourcing, determining and changing tastes. Customers and their habits, producer-supplier relationships, environmental issues, civil and legal laws, targeted subsidies, sanctions, political and economic relations, etc [11]. face countless opportunities and threats, which Examining these factors and determining the effects and severity of their effect will play an important role in the timely supply of parts and production in the entrepreneurship of these entrepreneurs and start-up entrepreneurs who enter this field.…”
Section: Introductionmentioning
confidence: 99%